Enhancing Teacher Performance in Madrasahs through Strategic Coaching Interventions - Kalsum, Kalsum; Humaeroah, Humaeroah; Agussalim, Agussalim (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study investigates the effectiveness of a coaching strategy in enhancing teacher performance at Madrasah Aliyah in Parepare. This type of research is quantitative descriptive research. The participants were all English teachers at Madrasah Aliyah in Parepare. The instrument in this study is a questionnaire, namely guide question coaching for teachers. The statistical procedures used include descriptive statistics for various items in the questionnaire calculated using SPSS (Statistical Product Services and Solutions). The research results found that analysis revealed that the predominant challenges faced by teachers included social competency issues (38%), professional competencies (28%), pedagogical challenges, and personal traits affecting student engagement (8%). The research found that the use of coaching strategy empowering the teacher’s performance at Madrasah by several indicator: 1) The question of coaching guide really explores the teachers’ competencies in knowing their self-strength (teachers); 2) The coaching guide question explore the teachers thinking competencies to realize and recognizing the teacher’s problem and redesigning step by step real action plan to move to the realization act; and 3) The coaching strategy bring the teachers into braveness to confidence to measure their progression in to the real number in percentage.